Pengaruh Pelatihan Soft Skills di CV Duta Capacitor terhadap Kinerja Karyawan - Merlydatul Wardiyati; Agung Dwi Nugroho (Pusat Riset dan Inovasi Nasional, 2025)
This research focused on exploring the impact of soft skills training on employee performance at CV Duta Capacitor. Qualitative methods were used in this study with data collection through in-depth interviews and direct observation. The subjects of this study were employees at CV Duta Capacitor who had attended soft skills training consisting of four employees involved in the training program. The results of this study show that soft skills training has a positive impact on employee performance in various aspects, such as improved communication skills, teamwork, discipline, time management, and individual initiative and responsibility. In addition, the training also contributed to increasing work motivation and shaping a more productive work culture. The results of this study highlight the importance of soft skills training for effective human resource development in organizations.